Regulamin szpitala bydgoskiego z pierwszej połowy XVII wieku (Kronika Bydgoska, 2012)
The first charitable institution in Bydgoszcz was the shelter of the Holy Spirit established on September 14, 1448. The foundation of the hospice and the church was confirmed in Włocławek by the official and curate generał of Włocławek bishop. The shelter was founded by the burghers. The patronage law belonged to the City Council, and the Church authorities established the local provostry. In the middle of the 17th century, a decision was madę to reconstruct the hospital. The principles of its functioning were regulated by new regulations. 30 items specified the issues connected with maintenance of the shelter, management of and keeping watch over the hospital, the number and principles of admittance and duties of inmates, nutrition conditions of the shelteris inmates, as well as types and sources of charity. The analysis of the regulations is complemented with the original Latin document.